2014
DOI: 10.1021/la501639z
|View full text |Cite
|
Sign up to set email alerts
|

Densification and Depression in Glass Transition Temperature in Polystyrene Thin Films

Abstract: Ellipsometry and X-ray reflectivity were used to characterize the mass density and the glass transition temperature of supported polystyrene (PS) thin films as a function of their thickness. By measuring the critical wave vector (qc) on the plateau of total external reflection, we evidence that PS films get denser in a confined state when the film thickness is below 50 nm. Refractive indices (n) and electron density profiles measurements confirm this statement. The density of a 6 nm (0.4 gyration radius, Rg) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
115
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(150 citation statements)
references
References 69 publications
18
115
3
Order By: Relevance
“…This can be explained by the scaling treatment of adsorption kinetics: [25,26] the surface coverage of early arriving chains that lie flat on the surface (i.e., the flattened chains) is a decreasing function of M w (below M w, c ) such that more free surface areas are available for late arriving chains that form bridges jointing up nearby empty sites (i.e., the loosely adsorbed chains). Such an increase in density at the polymer-solid interface is consistent with other experimental [27,28] and simulation results. [29,30] We further advanced the leaching conditions (type of a solvent, leaching time, leaching temperature, etc.…”
Section: Doi: 101002/macp201700326supporting
confidence: 92%
See 1 more Smart Citation
“…This can be explained by the scaling treatment of adsorption kinetics: [25,26] the surface coverage of early arriving chains that lie flat on the surface (i.e., the flattened chains) is a decreasing function of M w (below M w, c ) such that more free surface areas are available for late arriving chains that form bridges jointing up nearby empty sites (i.e., the loosely adsorbed chains). Such an increase in density at the polymer-solid interface is consistent with other experimental [27,28] and simulation results. [29,30] We further advanced the leaching conditions (type of a solvent, leaching time, leaching temperature, etc.…”
Section: Doi: 101002/macp201700326supporting
confidence: 92%
“…The choice of the twolayer model was determined by the corresponding FT profile of the XR profile, and the details of the data analysis have been described elsewhere. [2,3,6,33] The densification of the polymer chains in the vicinity of the substrate surface is in line with previous experimental [2][3][4]6,27,28] and simu lation findings. [19,20] The presence of the two-layer formation indicates that the irreversible adsorption of polymer chains on a solid surface is kinetically controlled: the later arriving polymer chains "reel-in" the empty spaces of the flattened layer, forming the outer loosely adsorbed polymer chains on the solid surface.…”
Section: Atomic Force Microscopy Measurementssupporting
confidence: 89%
“…For instance in ellipsometry, a technique employed to determine the temperature dependence of the thickness of films, normally cooling/heating rates of the order of 0.1 to 30-40 K/min are applied to determine the glass transition behaviour as a function of thickness [5,33,38,41,46,48,91,107,112,113]. Similar rates, or even smaller, are employed in fluorescent spectroscopy [34,93] and positron annihilation lifetime spectroscopy (PALS) [28,102], which both (indirectly and directly, respectively) measure the local free volume, X-ray reflectivity [71,102,113] and capacitive dilatometry (CD) [14,42,65,89]. In the case of conventional DSC, rates of the 30-40 K/min can be achieved [13,14,55,116].…”
Section: Cooling Rate Dependent Thermal Glass Transitionmentioning
confidence: 99%
“…However, such a transition is not evident in the present data. While thin films typically do show a different behavior compared to bulk materials, a film thickness greater than 100 nm (such as the ones used in this study) is often found in agreement with the bulk [2526]. …”
Section: Resultsmentioning
confidence: 97%